2021
DOI: 10.1021/acs.jafc.1c06473
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Key Odorants in Xinyang Maojian Green Tea and Their Changes During the Manufacturing Process

Abstract: Xinyang Maojian (XYMJ) green tea is a famous high-grade Chinese green tea, but the key odorants contributing to its aroma have been poorly understood. In this study, solid-phase microextraction and solvent-assisted flavor evaporation were used for sample preparation, and gas chromatography–mass spectrometry (GC–MS) and gas chromatography–olfactometry (GC–O) were used for both qualitative and quantitative analysis. A total of 50 volatile compounds of five chemical classes were identified in XYMJ tea infusion. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 50 publications
3
29
0
Order By: Relevance
“…All lipid degradation products, such as (E,E)-2,4-heptadienal, showed the highest concentrations in the fresh tea leaves but significantly lower concentrations in the final green tea [ 10 ]. Except for cis-3-hexenyl hexanoate, the concentrations of most aroma compounds decreased after fixation during the Xinyang Maojian (XYMJ) green tea manufacturing [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…All lipid degradation products, such as (E,E)-2,4-heptadienal, showed the highest concentrations in the fresh tea leaves but significantly lower concentrations in the final green tea [ 10 ]. Except for cis-3-hexenyl hexanoate, the concentrations of most aroma compounds decreased after fixation during the Xinyang Maojian (XYMJ) green tea manufacturing [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ‘green’ odor of tea is mainly attributed to C6 and C9 alcohols and aldehydes [ 19 ]. In PGT, high levels of esters such as ethyl hexanoate, cis -3-hexenyl acetate, ( E )-3-hexen-1-yl butyrate, butyl hexanoate, ethyl caprylate and ( Z )-3-hexen-1-yl caproate ( p < 0.05), endowed PGT with characteristic fruity and sweet odor notes [ 20 ]. Most of volatile compounds were formed by the enzymatic, hydrolysis and thermal cracking reactions in the mechanical damage and high temperature of leaves during processing [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Relatively long time of pan-fire fixation may cause alcohols with low boiling point to volatilize and promote the formation of esters by esterification reaction of alcohols and acids. Cui et al [ 20 ] have reported that the content of cis -3-hexenyl hexanoate increased after the fixation process of pan-fire, which may be formed from the esterification of cis -3-hexenol at high temperature.…”
Section: Resultsmentioning
confidence: 99%
“…However, AAs contents in different growth process involve both increasing contents attributed to protein break-down, hydrolysis, or cleavage and decreasing content due to their consumption as precursors of other compounds [ 5 , 6 ]. The dynamic changes are detrimental for determining the reasonable plucking seasons, especially for Xinyang Mao Jian (XYMJ), whose annual average temperature is lower than that of other green tea-producing areas in China [ 7 ]. The special environmental condition has a significant effect on the contents of AAs and the formation of tea quality.…”
Section: Introductionmentioning
confidence: 99%